2014
DOI: 10.1016/j.ijgo.2014.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Placental proteome alterations in women with intrahepatic cholestasis of pregnancy

Abstract: The placentas of women with ICP displayed significant proteome differences compared with women with a normal pregnancy. The results indicate that a variety of mechanisms and proteins may contribute to the development of ICP. Further verification and research are required to elucidate the exact roles of these proteins in ICP pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In our study, more proteins in the placental tissue were identified with higher resolution mass spectrometry, which is 3337, more DEPs including 37 upregulated and 141 downregulated proteins were found. Compared with He et al [ 14 ] study, only 37 DEPs were identified in the placental tissue of ICP patients compared with normal controls by the method of two-dimensional electrophoresis and mass spectrometry. In Zhang et al study [ 15 ], only 2120 proteins were identified in the placental tissue of ICP patients compared with normal controls by isobaric tags for relative and absolute quantification-based proteomics approach, including 29 upregulated proteins and 9 downregulated proteins.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, more proteins in the placental tissue were identified with higher resolution mass spectrometry, which is 3337, more DEPs including 37 upregulated and 141 downregulated proteins were found. Compared with He et al [ 14 ] study, only 37 DEPs were identified in the placental tissue of ICP patients compared with normal controls by the method of two-dimensional electrophoresis and mass spectrometry. In Zhang et al study [ 15 ], only 2120 proteins were identified in the placental tissue of ICP patients compared with normal controls by isobaric tags for relative and absolute quantification-based proteomics approach, including 29 upregulated proteins and 9 downregulated proteins.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, mass spectrometry based proteomics can be used to study the expression levels, isoforms and post-translational modifications of proteins. The present review collected a total of 9 proteomics studies of ICP (27)(28)(29)(30)(31)(32)(33)(34)(35), including 8 untargeted and 1 targeted studies (Table 2). There are three types of technologies for the analyses of untargeted proteomics studies, including: 2D-PAGE MS (two-dimensional polyacrylamide gel electrophoresis followed by mass spectrometry), DDA (data-dependent acquisition) based LC-MS/MS (Liquid chromatography-tandem mass spectrometry), and DIA (data-independent acquisition) based LC-MS/MS.…”
Section: Proteomics Strategiesmentioning
confidence: 99%
“…Comparative proteomics analysis found less differentially expressed proteins. He et al reported 37 differentially expressed proteins, which involved in cytoskeleton activity, blood coagulation, and platelet activation as well as chaperones, heat shock proteins, RNA-binding and calcium-binding proteins, and various enzymes [ 88 ]. Zhang et al found 38 differentially expressed proteins, among which 29 were upregulated and 9 were downregulated in ICP placenta [ 89 ].…”
Section: The Role Of Bile Acid and Its Receptorsmentioning
confidence: 99%